Address by Y.A.B. Dr. Lim Chong Eu, Chief Minister of Penang at the opening session of the Asian and Pacific Seminar on Consumer Testing And Research held at Recsam Gelugor at 9.00 a.m. on Monday 4th October 1976. - Lim, Chong Eu (1976)
It was some ten years ago when I first spoke in Malaysia Parliament on the subject of consumer organisation and the need for consumer protection.